Association Between 18-FDG Positron Emission Tomography and MRI Biomarkers of Plaque Vulnerability in Patients With Symptomatic Carotid Stenosis - Giannotti, Nicola; McNulty, Jonathan; Foley, Shane; McCabe, John; Barry, Marey; Crowe, Morgan; Dolan, Eamon; Harbison, Joseph; Horgan, Gillian; Kavanagh, Eoin; O'Connell, Martin; Marnane, Michael; et al. (Frontiers in Neurology, 2021)
Purpose: Pathologic studies suggest that unstable plaque morphology and inflammation are associated with cerebrovascular events. 18F-fluorodeoxyglucose positron emission tomography (18FDG-PET) is a validated technique for non-invasive imaging of inflammation-related plaque metabolism, and MRI can identify morphologic features of plaque instability. The aim of this study was to investigate the association of selected imaging characteristics of plaque vulnerability measured with MRI and PET in patients with symptomatic carotid stenosis. Methods: Patients from the BIOVASC study were selected based on the following inclusion criteria: (1) age ≥ 50 years; (2) recent (<30 days) ischaemic stroke (modified Rankin scale ≤3) or motor/speech/vision TIA; (3) ipsilateral internal carotid artery stenosis (≥5 0% lumen-narrowing); (4) carotid PET/CTA and MRI completed. Semi-automated plaque analysis of MRI images was performed to quantify morphologic features of plaque instability. PET images were co-registered with CTA and inflammation-related metabolism expressed as maximum standardised uptake value (SUVmax). Results: Twenty-five patients met inclusion criteria (72% men, mean age 65 years). MRI-measured plaque volume was greater in men (1,708–1,286 mm3, p = 0.03), patients who qualified with stroke (1,856–1,440 mm3, p = 0.05), and non-statin users (1,325–1,797 mm3, p = 0.03). SUVmax was associated with MRI-measured plaque lipid-rich necrotic core (LRNC) in the corresponding axial slice (rs = 0.64, p < 0.001) and was inversely associated with whole-plaque fibrous cap thickness (rs = −0.4, p = 0.02) and calcium volume (rs = −0.4, p = 0.03). Conclusion: This study demonstrated novel correlations of non-invasive imaging biomarkers of inflammation-related plaque metabolism with morphological MRI markers of plaque instability. If replicated, our findings may support the application of combined MRI and PET to detect vulnerable plaque in future clinical practise and randomised trials.